ANALISIS PENGARUH TOTAL DRY SOLID BLACK LIQUOR TERHADAP EFISIENSI RECOVERY BOILER - Sumarna, Herlin; Hidayati, Baiti; Ramadhoni, Tri Satya; Okviyanto, Toni; Anwar, Zainuri; Rifa’i, Ahmad Imam (Politeknik Negeri Sriwijaya, Indonesia, 2023)
In the pulp and paper industry, a large amount of biomass (wood) has been used and produces by-products or residues resulting from the industry including wood bark, remaining logging and black liquor which is one of the main biomass resources that can be used for energy purposes. Aside from being a fuel, the recovery boiler process can convert black liquor into green liquor, where green liquor will be needed in the pulp production process. Writing this journal aims to determine the effect of total dry solids in black liquor on the efficiency of recovery boilers. The analysis was carried out using energy calculations in the recovery boiler for five days. From the calculation results it is known that there is a decrease and increase in boiler recovery efficiency, this is caused by several factors, including the heat absorption process experienced by the boiler feed water, the mass of black liquor, and the percentage of total dry solids. The total dry solid will affect the water content that will enter the combustion chamber, the higher the % TDS the more water content will enter the combustion chamber and this will affect the recovery efficiency of the boiler. The highest boiler recovery efficiency calculation results occurred on the first day, namely 65.24% and the lowest boiler recovery efficiency calculation results occurred on the fourth day, namely 62.96%.